Beyond the informal sector. Labour absorption in Latin American urban economies. the case of Colombia. Francisco Uribe-Echevarría - Uribe-Echevarría, Francisco (ISS, 1991)
Análisis sobre empleo y desempleo en Colombia, y el rol del empleo urbano en el sector informal